AN ANALYSIS OF DENOTATIVE AND CONNOTATIVE MEANING SELECTED JUSTIN FT KID LAROI SONGS LYRIC - Gee, Rosnita; Laiya, Rebbeca E.; Telaumbanua, Tatema (Research on English Language Education, 2022)
Denotative meaning is the original meaning or a true meaning possessed by a lexeme. Connotation is related to value of the sense of people who use language, whether they fell happy, sad, repugnant and angry. The purposes of this research were to identify the types of connotative meaning in Kid laroi song lyrics and describe the meaning of denotative and connotative meaning in Kid laroi song lyric. The method of the research was qualitative descriptive method. The data was obtained from song lyrics of Kid laroy song lyrics. The data was collected by downloading Kid laroy selected songs, listening all of Kid laroy songs, finding the words, phrases or sentences which consists of denotative and connotative meanings, then analyzing the words, phrases and sentences which found out. The data was analyzed based on Miles et al theory. From the result, researcher found three types, they are (1) Positive Connotative 8 data in ten lyrics of kid laroi song (2) negative connotative 14 data in ten lyrics of kid laroy song. (3) Neutral connotative 1 data in ten lyrics of kid laroi song. Based on the result, it is concluded that, the researcher got are 23 connotative meaning, and 15 dennotative meaning there could be found is Kid Laroi album. Based on the conclusion, the researcher would give contribution for the college students especially at English department, than, lyrics of Kid laroi can be used as a material college students to broaden and develop their knowladge about denotative and connotative meaning and both of the types connotative meaning in the song lyrics. And also for the readers or the next researcher, the researcher suggested that, this research can be used as a conception and reference in conducting research related to denotative and connotative meaning.